Social Confrontation with Menstruation: A Feminist Ethnography of Menstrual Experience among Female Instagram Users - Rana Mohammad Taghinejad Esfahani; Majid Movahed; Halimeh Enayat; Aliyar Ahmadi (جامعه شناسی کاربردی)
IntroductionPatriarchy has systematically marginalized many issues related to women, including their biological experiences, such as menstruation, pregnancy, and childbirth, by relegating them to personal rather than social matters. As a result, women's issues have rarely been addressed in public discourse or socio-political discussions. Historically, in many cultures and religions, menstruation has been viewed as "unclean" and "taboo" (Buckley & Gottlieb, 1989), leading to its characterization as undesirable and shameful. Consequently, many women refrain from sharing their experiences or challenging the taboos surrounding menstruation in public, confining this natural process to the private sphere. Women’s biological experiences are profoundly influenced by power dynamics and cultural contexts. The marginalization of these experiences in private spaces necessitates their reintroduction and emphasis in public, cultural, and academic discussions. Acknowledging this is crucial as menstruation is an inherent part of every woman's life and has significant implications for their physical, mental, and social health. Addressing this issue is vital not only for improving public awareness and acceptance of menstruation, but also for combating gender and bodily discrimination, supporting women’s rights and health, and dismantling cultural taboos. However, due to the lack of proper information and education, as well as  the persistence of cultural taboos, many women experience feelings of shame and isolation during menstruation, resulting in their exclusion from public spaces. Therefore, structural changes in power and culture are essential for redefining women’s issues. Instagram as a social network that offers a free and visual platform plays a crucial role in dismantling socio-cultural taboos. Many social activists, feminists, and health brands leverage this space to share educational content on the menstrual cycle, hygiene products, and menstrual management through posts and stories. These efforts aim to shift negative attitudes and enhance public awareness on the subject. This study examined women’s experiences of menstruation on Instagram and explored how menstruation taboos function as mechanisms for controlling women’s bodies within the existing power structures and daily life. It also investigated the tools and strategies used to increase awareness and acceptance of this natural process within the society. By integrating the theories of Foucault and Kristeva, we gained insight into how this natural phenomenon was influenced by social, cultural, and discursive powers, as well as how the taboos surrounding menstruation shaped women’s lived experiences. Furthermore, these theories allowed us to explore the representation of women’s bodies and menstruation in virtual spaces like Instagram, revealing how socio-cultural powers were exercised through the female body and how menstruation remained marginalized as a shameful and impure topic. However, social media provided a platform for women to challenge these power structures and share their experiences.   Materials & MethodsThis research employed feminist ethnography, utilizing Charmaz Grounded Theory for data analysis. Feminist ethnography is a research approach rooted in feminist principles that not only considers individuals' experiences and perspectives within their social contexts, but also emphasizes power dynamics, gender inequalities, and representation of women and marginalized groups. This approach allowed the researchers to critically examine findings, amplifying the experiences and voices of those on the margins rather than relying solely on dominant societal narratives. It asserted that the everyday experiences of women often overlooked warranted serious study.When the initial idea for this article took shape, we began with non-participatory observation by visiting pages that shared content about menstruation and women's bodies. I actively engaged with these pages through likes and comments, collecting a wealth of information, screenshots, and field notes. Gradually, we transitioned from an observer to an active participant by sharing posts and question boxes related to menstruation on our private Instagram pages. We then selected participants from our followers and those we followed. All participants were women, who had experienced menstruation, were active on Instagram, and were willing to discuss the topic.Participants were initially selected through purposeful and convenience sampling followed by snowball sampling. This process continued until theoretical saturation was reached, ensuring that no new categories emerged and theoretical sufficiency was achieved. Semi-structured interviews were conducted with 30 individuals, who also identified Instagram pages, such as Mahsa Mousavi (a midwifery page), Zagah, Nabat Etemad, Farank Amidi, and Levva.Pharma, as valuable sources of information on menstruation. Additionally, screenshots were randomly collected from posts or stories by popular bloggers discussing the topic.To validate the results, 6 participants were given their interview transcripts for review. After receiving their approval, the analysis process was discussed with two methodology experts. Subsequently, using triangulation, the codes derived from the analysis were reviewed by specialists, yielding consistent results. The interviews were carefully transcribed and incorporated into the text. Given the qualitative nature of this research, the findings were context-specific, while different outcomes might emerge in other settings with different participants. Discussion of Results & ConclusionWe analyzed the social experiences of our participants, each of which, while unique, shared commonalities with others. Despite their differences, these experiences were shaped by patriarchal structures. Utilizing feminist ethnography and Charmaz grounded theory, this research provided a critical exploration of women’s experiences related to menstruation. The aim was to amplify the voices of women whose life experiences—such as housework, cooking, menstruation, and breastfeeding—were often dismissed as insignificant. Each woman’s story served as the foundation for this analysis.The central category identified was "menstruation as a social construct", which encompassed 8 main subcategories: menstruation as "becoming a woman", discovery of menstruation, women’s social life during menstruation, digitalization of menstruation awareness, presence or absence of legal support, menstruation as a social taboo, menstruation as a source of social shame, and men's encounters with women’s menstruation. These categories emerged from the contributions of women active on Instagram.The experience, perception, and acceptance of menstruation are influenced not only by biological factors, but also by social, cultural, and historical contexts. Attitudes toward menstruation vary across cultures shaped by social norms and power structures that can evolve over time. Women’s resistance to restrictive discourses manifests in awareness-raising efforts, open discussions about menstruation, participation in social movements that challenge taboos, and advocacy for healthcare rights. Understanding menstruation as a social construct is crucial for addressing related inequalities. By increasing awareness and providing appropriate education, we can enhance women’s understanding and experiences of menstruation, transforming it into a more positive and constructive process.In this study, participants shared how taboos and misconceptions surrounding menstruation had adversely affected women. Religious and traditional beliefs, the role of family, the educational system, and mass media had all contributed to reinforcing these taboos. However, the silence surrounding menstruation was gradually being broken through discussions on platforms like Instagram. In this space, women learned to observe their bodies, ask questions, and engage constructively with their own experiences. As this discursive space evolves, menstruation is continually reconstructed by a new generation of women. Understanding menstruation as a social construct allows us to recognize how women's bodies are shaped by power dynamics, resistance, and gender norms. Instagram serves as a platform for re(constructing) the menstrual experience, enabling individuals to redefine their own narratives, challenge gender taboos, and create an environment conducive to changing negative norms and attitudes.By employing Foucault’s concept of bio-power and Kristeva’s notion of abjection, this study illustrated how social and cultural systems influenced women’s bodies and how their experiences of menstruation were reflected in both social and digital spaces like Instagram. The research revealed the diversity and depth of women’s experiences in confronting menstruation-related taboos and stigmas, offering a more nuanced understanding of the subject. Menstruation was not merely a biological process; it was intertwined with social, cultural, political, and economic structures. Through sharing their experiences, women were transforming the narrative around menstruation, breaking the stigma, and paving the way for a more informed, open, and compassionate society where women could discuss their issues freely, without fear or shame.